Oxford Understanding History 3 - Ismat Riaz (Karachi: Oxford University Press., 2024)
Oxford Understanding History 3 delves into modern history, exploring key events, movements, and figures from the 18th century to the contemporary era. The textbook provides detailed accounts of significant developments such as revolutions, industrialization, world wars, and decolonization, helping students understand their global impact. With a focus on critical thinking, students are encouraged to analyze historical sources, assess different perspectives, and make connections between past events and current global issues. Through maps, timelines, and engaging narratives, the book deepens students' understanding of modern history, preparing them for advanced historical studies while fostering a global awareness of the past's influence on today's world.